Study of subwavelength structures for optical beam focusing and laser cavity - Mote, Rakesh Ganpat (2011)
With the rapid development of microelectronic industry of data processing, data storage/reading, and various optoelectronic devices, the demand for small-sized optical components and optical systems is increasing. Diffractive optics has a potential to improve optical systems by increasing their reliability, robustness, and functional integration, while reducing their sizes. The present work investigated diffractive optical elements with subwavelength features for near-field focusing and laser cavity. Fresnel zone plates (FZPs) in the visible wavelengths were studied for near-field focusing. In addition, for laser cavity reflectors, 2-dimensional grating based on high-index-contrast materials was investigated. Near-field focusing properties of FZPs were investigated in the visible regime by a 3-dimensional finite-difference time-domain (FDTD) method. It was proposed to use phase zone plate structured on a glass to improve the diffraction efficiency of subwavelength focusing. Furthermore, a simple analytical model was used to show that high numerical aperture phase FZP under the linearly polarized illumination produces a rotationally asymmetric focal spot. With a radially polarized illumination, rotationally symmetric focal spot with a minimum beamwidth of 0.39l is obtained. Focusing behavior of phase FZPs fabricated using Focused ion beam (FIB) was characterized by near-field scanning optical microscope (NSOM) and shown to be in agreement with the simulation results. The use of a 2-dimensional high-index-contrast grating (HCG) with a square periodic lattice is proposed to realize surface-emitting lasers. With a suitable design of the 2-dimensional HCGs, Q factor as high as 1032 was achieved.